Повышение точности печати 3D принтера путем использования индуктивного датчика - Емцов, Н. П.; Глухов, О. В. (ХНУРЕ, 2019)
We considered the problem of adjusting the table 3d printer and its solution in the form of an inductive sensor LJ18A3-8-Z / BX. The use of this sensor has improved the printing accuracy by two orders.
Keywords: Повышение точности печати; 3D принтер; индуктивный датчик